Foundations of Molecular Modeling and Simulation Select Papers from FOMMS 2015 - Snurr, Randall Q.; Adjiman, Claire S.; Kofke, David A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book is a collection of select proceedings of the FOMMS 2015 conference. FOMMS 2015 is the sixth triennial FOMMS conference showcasing applications of theory of computational quantum chemistry, molecular science, and engineering simulation. The theme of the 2015 meeting focuses on Molecular Modeling and the Materials Genome.
A Discontinuous-Potential Model for Protein-Protein Interactions -- Probing How Defects in Self-Assembled Monolayers Affect Peptide Adsorption with Molecular Simulation -- Development of a Coarse-Grained Water Forcefield Via Multistate Iterative Boltzmann Inversion -- Optimizing Molecular Models through Force Field Parameterization via the Efficient Combination of Modular Program Packages -- A Hierarchical, Component Based Approach to Screening Properties of Soft Matter -- Quantum Virial Coefficients via Path Integral Monte Carlo with Semi-Classical Beads -- Homogeneous Nucleation of [Dmim+][Cl-] from its Supercooled Liquid Phase: A Molecular Simulation Study -- Influence of the Precursor Composition and Reaction Conditions on Raney-Nickel Catalytic System -- Atomistic Modeling and Simulation at Solving Gas-Extraction Problems -- Atomistic Simulations of CO2 During "Trapdoor" Adsorption Onto Na-Rho Zeolite.
Keywords: Biotechnology; Engineering mathematics; Engineering -- Data processing; Medicine -- Research; Biology -- Research; Materials -- Analysis; Chemical Bioengineering; Mathematical and Computational Engineering Applications; Biomedical Research; Characterization and Analytical Technique